Qualidade fisiológica de sementes de genótipos de algodoeiro sob estresse salino - Lima, Leonardo Henrique Guedes de Morais (2007)
The germination of cotton seeds and the seedlings emergency are generally delayed and reduced by the salinity. Although the cotton is considered a tolerant culture, it can suffer substantial reductions in regarding its growth and production when exposed to salinity condition. The aims of this study went evaluate the effect of the saline stress in the germination phase to four cotton genotypes (BRS Rubi, BRS Safira, BRS 201 and CNPA 187 8H), using different osmotic potentials generated with increment of sodium chloride (NaCl). The saline stress was simulated using NaCl aqueous solutions in the potentials: 0.0 (Control); -0.2; -0.4; -0.6; -0.8 and -1.0 MPa. The treatments were monitored by means of tests for analysis of seeds, germination, first counting, speed germination index, length of shoot, radicle length, dry weigth of embrionic axis and shoot/radicle ratio. The tests for germination, first counting and index of germination speed were accomplished using 50 seeds for repetition and for the study of length of shoot, radicle length, dry weigth of embrionic axis and shoot/radicle ratio were used 20 seeds by repetition. For both tests four repetitions were accomplished by genotype for each one of the potentials. The seeds of each repetition were involved in papers Germitest humidified with NaCl solution corresponding to the potential. The repetitions of both tests were maintained in a germinator with saturated humidity. The analysis were initiate four days after the induction of the saline stress. The evaluations of the first three variables analyzed were accomplished daily; the seeds were remove and counted when its germinated. For the length tests just the repetitions corresponding to the potential of NaCl 0,0 MPa were analysis 4 days after the beginning of the induction of the saline stress. The analysis of the repetitions of the potentials -0,2 and -0,4 and of the potentials -0,6, -0,8 and -1,0 MPa they were accomplished with 12 and 20 days, respectively. For accomplishment of the analisis of this test the shoot of the 20 plantules of each repetition was separate from the radicle and both parts were measured. The statistical analyses were performed using the GENMOD and GLM procedures of the SAS. For the variable germination, the cultivates CNPA 187 8H and BRS Safira stood out for the potential -0.8 MPa, with averages of 89% and 81%, respectively. The test of speed germination index to cultivate BRS Safira presented the largest averages for the two higher saline potentials. It was observed that the increase of the saline potential reduces the germination percentage and speed germination index. For each day of evaluation it was verified that the increase of the saline potential causes a reduction of the length both of the shoot and of the radicle. The radicle tends to grow more than the shoot until the potential -0,4 MPa